Commercially Available Textiles as a Scaffolding Platform for Large-Scale Cell Culture - Agarwal, Tarun; Tan, Sheri-Ann; Rathnam Vuppaladadium, Shanmuga Sharan; Sajja, Tanmayi; Maiti, Tapas Kumar (International Journal of Biomaterials, 2023)
The present study outlines the evaluation of textile materials that are currently in the market for cell culture applications. By using normal LaserJet printing techniques, we created the substrates, which were then characterized physicochemically and biologically. In particular, (i) we found that the weave pattern and (ii) the chemical nature of the textiles significantly influenced the behaviour of the cells. Textiles with closely knitted fibers and cell adhesion motifs, exhibited better cell adhesion and proliferation over a period of 7 days. All the substrates supported good viability of cells (>80%). We believe that these aspects make commercially available textiles as a potential candidate for large-scale culture of adherent cells.